Distortions to Agriculture and Economic Growth in Sub-Saharan Africa - Anderson, Kym; Brückner, Markus (World Bank, Washington, DC, 2013)
To what extent has Sub-Saharan Africa's slow economic growth over the past five decades been due to price and trade policies that discouraged production of agricultural relative to non-agricultural tradables? This paper uses a new set of estimates of policy induced distortions to relative agricultural prices to address this question econometrically. First, the authors test if these policy distortions respond to economic growth, using rainfall and international commodity price shocks as instrumental variables. They find that on impact there is no significant response of relative agricultural price distortions to changes in real GDP per capita growth. Then, the authors test the reverse proposition and find a statistically significant and sizable negative effect of relative agricultural price distortions on the growth rate of Sub-Saharan African countries. The fixed effects estimates yield that, during the 1960-2005 period, a ten percentage points increase in distortions to relative agricultural prices decreased the region's real GDP per capita growth rate by about half a percentage point per annum.